Associations of human milk oligosaccharides and bioactive proteins with infant growth and development among Malawian mother-infant dyads. Issue 1 (23rd October 2020) - Jorgensen, Josh M; Young, Rebecca; Ashorn, Per; Ashorn, Ulla; Chaima, David; Davis, Jasmine C C; Goonatilleke, Elisha; Kumwenda, Chiza; Lebrilla, Carlito B; Maleta, Kenneth; Prado, Elizabeth L; Sadalaki, John; et al.
ABSTRACT: Background: Human milk oligosaccharides (HMOs) and bioactive breast milk proteins have many beneficial properties. Information is sparse regarding associations between these milk constituents and infant growth and development in lower-income countries. Objectives: We aimed to examine associations of milk content of HMOs and bioactive proteins at 6 mo postpartum with infant growth and motor and cognitive development. These are secondary analyses of a randomized controlled trial in rural Malawi. Methods: Breast milk samples were analyzed at 6 mo ( n  = 659) for general categories of HMOs (total HMOs, fucosylated HMOs, and sialylated HMOs), 51 individual HMOs, and 6 bioactive proteins (lactalbumin, lactoferrin, lysozyme, antitrypsin, IgA, and osteopontin). We examined associations of the relative abundances of HMOs and concentrations of bioactive proteins with infant growth from 6 to 12 mo [change in length-for-age (ΔLAZ), weight-for-age, weight-for-length, and head circumference z -scores] as well as ability to stand or walk alone at 12 mo, and motor and language skills, socioemotional development, executive function, and working memory at 18 mo. Analyses were adjusted for covariates and multiple hypothesis testing. Results: Among all participants, there were inverse associations of IgA and lactoferrin concentrations with motor skills ( P  = 0.018 and P = 0.044), and a positive association of lactalbumin concentration with motor skills ( P  = 0.038). Among secretors only [fucosyltransferase 2 gene ( FUT2 ) positive], there were positive associations of absolute abundance of HMOs with ΔLAZ ( P  = 0.035), and relative abundance of fucosylated and sialylated HMOs with language at 18 mo ( P  < 0.001 and P  = 0.033, respectively), and inverse associations of osteopontin with standing and walking at 12 mo ( P  = 0.007 and 0.002, respectively). Relative abundances of several individual HMOs were associated with growth and development, mostly among secretors. Conclusions: Certain bioactive breast milk proteins and HMOs are associated with infant growth and motor and cognitive development. Further studies are needed to determine if a causal relation exists. This trial was registered at clinicaltrials.gov as NCT01239693.